PENGARUH KOMPETENSI SUMBER DAYA MANUSIA DAN PENGENDALIAN INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAHAN KOTA MEDAN - Zepanya Okta Sari Simanjuntak; Melanthon Rumapea; Rasmulia Sembiring (Universitas Methodist Indonesia, 2023)
This study aims to determine and analyze the effect of resource competence and internal control on the quality of financial reports in the Medan City Government. This type of research is causal research using a quantitative approach. A sample of 80 samples consisting of 11 Regional Secretariats as many as 44 people, 2 DPRD Secretariats as many as 8 people, 4 Inspectorates as many as 16 people, and 3 Regional Offices as many as 12 people in Medan City. The data analysis technique used is multiple linear regression. The results of this study indicate that Human Resource Competence and Internal Control partially and simultaneously have a positive and significant effect on the Quality of Medan City Government Financial Reports. Competence of Human Resources and Internal Control can affect the Quality of Financial Statements by 66.4% and the remaining 33.6% can be influenced by other factors not examined such as the Application of Financial Accounting Systems because these factors are thought to affect the Quality of Financial Statements optimally.